The Congo trials in the International Criminal Court - Gaskins, Richard H. (Cambridge : Cambridge University Press, 2022)
This is the first in-depth study of the first three ICC trials: an engaging, accessible text meant for specialists and students, for legal advocates and a wide range of professionals concerned with diverse cultures, human rights, and restorative justice. Now with an updated postscript for the paperback edition, it offers a balanced view on persistent tensions and controversies. Separate chapters analyze the working realities of central African armed conflicts, finding reasons for their surprising resistance to ICC legal formulas. The book dissects the Court's structural dynamics, which were designed to steer an elusive middle course between high moral ideals and hard political realities. Detailed chapters provide vivid accounts of courtroom encounters with four Congolese suspects. The mixed record of convictions, acquittals, dissents, and appeals, resulting from these trials, provides a map of distinct fault-lines within the ICC legal code, and suggests a rocky path ahead for the Court's next ventures.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: International Criminal Court; War crime trials -- Netherlands -- Hague; War crimes -- Congo (Democratic Republic) -- Ituri Region